Spatial optical transmitter based on on/off keying line coding modulation scheme for optimum performance of telecommunication systems - Hazem M. El-Hageen; Aadel M. Alatwi; Ahmed Nabih Zaki Rashed (Indonesian Journal of Electrical Engineering and Computer Science, 2021)
This study has presented a spatial optical transmitter based on on off keying line coding modulation scheme for the optimum performance of telecommunication systems. The encircled flux versus fiber core radius, the 3D graph for fiber mode versus core radius, and the signal power level in dBm versus wavelength through coarse wavelength division multiplexing with a fiber length of 20 km are presented and discussed in detail. The total power measured in W and dBm as well as the signal power amplitude level obtained through the infinite impulse response (IIR) filter based on both Z domain and pole/zero coefficient filter types are illustrated clearly. Signal gain, noise figure, maximum Q factor, and received power are also clarified against bit rates for various modulation line coding schemes.